STUDI IMPLEMENTASI PEMANFAATAN MEDIA PEMBELAJARAN IPA KELAS IV DI MI MAZRO’ATUL ULUM 01 PACIRAN LAMONGAN - Dwi Ristikawati; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study was to observe the use of fourth grade science learning media at MI Mazr'atul Ulum 01 Paciran in May 2019. researchers used descriptive qualitative methods. The class observed in this study was the fourth grade students. The observation was carried out for 3 days to see the condition of the class during science learning and student learning outcomes after using learning media and before using learning media. this can be proven by the use of learning media that is still very minimal used by teachers. the lack of use of media is sometimes caused by constraints that exist in the school, among others: lack of support from the principal, the lack of learning media provided by the school. so that it can be concluded based on the results of these studies that the use of science learning media is very influential on the learning outcomes of fourth grade students MI Mazro'atul Ulum 01 Paciran in May 2019. Keywords: Utilization of Science Learning Media.